THE APPLICATION OF MECHANICAL DESKTOP IN AN EMBEDDED BEAM EFFORTS ANALYSIS - Martínez Silva, Luis (2004)
The present article shows an application of the efforts analysis using the Mechanical Desktop 6.0 Software, with the purpose of determining the efforts of a beam subjected to a punctual force. Calculations development is set by applying a 200N force to a 400x300x3000 mm dimension beam.